Perlindungan Hukum Terhadap Indikasi Geografis Papua Di Desa Maribu Kapubaten Jayapura - Pelupessy, Sella Petrix; Pelupessy, Berd Elkiopas; Pelupessy, Eddy; Reba, William H.; Sawen, Kristina; Kaplele, Farida; Palit, Silvester Magnus Loogman; Ketaren, Dahliana; Palenewen, James Yoseph; Tanati, Daniel; Ringgi, Deppa; Wulandari S, Lestari; Krey, Thresia Hilda M.Y. (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This service is carried out with the title Legal Protection of Geographical Indications of Papua in Maribu Village, Jayapura Regency, an activity carried out for partners with the aim that the community can know and understand the existence of legal protection for Geographical Indications of Papua in Jayapura Regency. The output of this service is to provide an understanding to partners about efforts to map geographical indications carried out to determine the limits of cases of violation of geographical indications so that holders of geographical indication rights can file lawsuits against users of geographical indications without rights, in the form of compensation payments and termination. Use and destruction of geographical indication labels used without rights through registration and publication. Geographical indications are protected as long as the reputation, quality and characteristics that are the basis for granting geographical indication protection to an item are maintained. And protection will be removed if these provisions are not met, and/or are contrary to state ideology, legislation, morality, religion, decency and public order. Therefore, Geographical indication mapping must be arranged in a geographical indication document that can be proven to be true. The procedure for submitting geographical indications and the procedure for registering geographical indications have been identified. Legal protection for geographical indications can be carried out in preventive and repressive forms. Preventive means preventive measures through refusal of registration and repressive payment of compensation.